Just Expect It: Compound Heterozygous Variants of POMT1 in a Consanguineous Family—The Role of Next Generation Sequencing in Neuromuscular Disorders - von der Hagen, Maja; Becker, Lena-Luise; Wienker, Thomas F.; Smitka, Martin; Musante, Luciana; Ropers, Hans-Hilger; Huebner, Angela; Hu, Hao; Kaindl, Angela M. (Neuropediatrics, 2020)
Muscular dystrophy-dystroglycanopathies (MDDG) are a group of genetically heterogeneous autosomal recessive disorders characterized by hypoglycosylation of α-dystroglycan. Here, we report on two female patients from a consanguineous Lebanese family that presented in early infancy with generalized muscle hypotonia and primary microcephaly. Brain magnetic resonance imaging (MRI) showed different degrees of hypoplasia of the cerebellar vermis and hypoplasia of corpus callosum. Muscle biopsy analyses revealed a muscular dystrophy with reduced expression of α-dystroglycan and merosin in immunoblot analyses. Homozygosity mapping failed to elucidate the causal mutation due to the accepted notion that, in consanguineous families, homozygote mutations cause disease. However, by applying whole exome sequencing, we identified a novel compound heterozygous POMT1 mutation that segregates with the phenotype and is in line with the clinical presentation. This underscores that a less expected compound heterozygous instead of homozygous mutation in a consanguineous marriage results in a recessive disorder and highlights the growing role of next generation sequencing in neuromuscular disorder diagnostics.
Keywords: compound heterozygosity; consanguineous; POMT1; congenital muscular dystrophy dystrogylcanopathies; developmental delay; microcephaly